KUALITAS AIR BAKU UNTUK DEPOT AIR MINUM AIR ISI ULANG (STUDI KASUS DI DEPOT AIR MINUM ISI ULANG ANGKE TAMBORA) - Puspitarini, Rizqa; Ismawati, Riva (Universitas Andalas, 2022)
Water for consumption purposes must be standardized, in terms of quality, physical, chemical and biological parameters, therefore will not cause side effects to health. Water quality standards indicate the recommended and permitted concentration value for all parameters. This research aims to examine the quality of water sourced from the Salak mountain springs. The location of clean water sampling was carried out on Ciapus Mount Salak raw water. Water quality test results from physical parameters of clean water including turbidity, color, total dissolved solid, temperature and odor have. Chemical parameters int the clean water standard are pH, iron, fluoride, hardness, Manganese, Nitrate, nitrite, cyanide, mercury, arsenic, cadmium, chromium, selenium, zinc, sulfate, lead and organic. Biological parameters of clean water including MPN coliform and Escherichia coli have standardized quality standards. Based on research results that all parameter of clean water including physical, chemical and biological have standardized quality can used to treatment drinking water.Keywords: clean water, drinking water, water quality standard, chemical parameter, biological parameterABSTRAKAir yang dikonsumsi harus memenuhi standar kualitas fisika, kimia dan biologi agar tidak menimbulkan efek samping bagi kesehatan. Baku mutu kualitas air mengidikasikan batas kadar tertinggi yang disarankan untuk semua parameter. Penelitian ini bertujuan menguji kualitas air yang bersumber dari mata air Gunung Salak. Parameter uji kualitas air fisika meliputi kekeruhan, warna, padatan terlarut, suhu dan bau. Parameter uji kualitas air kimia meliputi pH, besi, fluorida, kesadahan, mangan, nitrat, nitrit, sianida, merkuri, arsen, kadmium, khromium, selenium, seng, sulfat, timbal dan zat organik. Parameter uji kualitas air fisika meliputi MPN coliform and Escherichia coli. Berdasarkan hasil penelitian menunjukkan bahwa semua parameter kualitas air bersih yang meliputi fisika, kimia dan biologi memenuhi baku mutu yang dapat digunakan bahan baku pengolahan air minum.Kata Kunci: air bersih, air minum, standar kualitas air, pamateter kimia, parameter fisika